Flame spray pyrolyzed carbon-encapsulated Au/Fe3O4 nanoaggregates enabled efficient photothermal therapy and magnetic hyperthermia of esophageal cancer cells - Wang, Zida; Liu, Gongzhe; Zhou, Jiangping; Zhao, Xiaogang; Cai, Jie (Frontiers in Bioengineering and Biotechnology, 2024)
Multifunctional magneto-plasmonic nanoparticles with magnetic hyperthermia and photothermal therapy could kill cancer cells efficiently. Herein, carbon-encapsulated Au/Fe3O4 (Au/Fe3O4@C) was fabricated using an enclosed flame spray pyrolysis. The nanostructures, including an Fe3O4 core (51.9–55.2 nm) with a decreasing carbon shell thickness and an Au core (4.68–8.75 nm) coated with 2–4 graphite layers, were tailored by tuning the C2H4 content in the reacting gas mixture. Saturation magnetization (33.7–48.2 emu/g) and optical absorption were determined. The carbon shell facilitated the dispersion of Au/Fe3O4 and restrained their laser-induced and magnetic field-induced coalescence and growth. Au/Fe3O4@C exhibited excellent magnetic resonance imaging capability (91.4 mM−1 s−1) and photothermal performance (65.4°C for 0.8 mg/mL Au/Fe3O4@C at a power density of 1.0 W/cm2 after 300 s near-IR laser irradiation (808 nm)). Moreover, the combined application of photothermal and magnetic-heating properties reduced the required intensity of both laser and magnetic field compared to the intensity of separate situations. Our work provides a unique, intriguing approach to preparing multicomponent core/shell nanoaggregates that are promising candidates for esophageal cancer cell therapy.